2017
DOI: 10.1038/cddis.2017.463
|View full text |Cite|
|
Sign up to set email alerts
|

Superoxide drives progression of Parkin/PINK1-dependent mitophagy following translocation of Parkin to mitochondria

Abstract: Reactive oxygen species (ROS) and mitophagy are profoundly implicated in the pathogenesis of neurodegenerative diseases, such as Parkinson’s disease (PD). Several studies have suggested that ROS are not involved in mitochondrial translocation of Parkin which primes mitochondria for autophagic elimination. However, whether ROS play a role in the execution of mitophagy is unknown. In the present study, we show that carbonyl cyanide m-chlorophenylhydrazone (CCCP) treatment induced both mitochondrial depolarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 31 publications
5
72
0
Order By: Relevance
“…However, the treatment of pro-oxidant alone was insufficient to induce translocation of Parkin to mitochondria or autophagic clearance of mitochondria. Moreover, it was also shown that the p38 signaling pathway may contribute to the progression of mitophagy induced by ROS [281]. This result agrees with those of previous authors reporting that the MAPK signaling pathway was required for mitophagy in Saccharomyces cerevisiae [282] and HeLa cells [283].…”
Section: Ros and Mitophagysupporting
confidence: 91%
“…However, the treatment of pro-oxidant alone was insufficient to induce translocation of Parkin to mitochondria or autophagic clearance of mitochondria. Moreover, it was also shown that the p38 signaling pathway may contribute to the progression of mitophagy induced by ROS [281]. This result agrees with those of previous authors reporting that the MAPK signaling pathway was required for mitophagy in Saccharomyces cerevisiae [282] and HeLa cells [283].…”
Section: Ros and Mitophagysupporting
confidence: 91%
“…In these cells, pretreatment with GSHee, a membrane-permeable derivative of GSH that recovers the mitochondrial GSH content and inhibits A -induced ROS [18,26], completely abolished the presence of mitochondrial PINK1 and mitophagosomes formation. These data complement previous studies that illustrate how modulation of the mitochondrial antioxidant protein superoxide dismutase-2 has a direct impact on mitophagy progression, and point to mitochondrial ROS production as an upstream inducer of the process [61,66,67].…”
Section: Discussionsupporting
confidence: 89%
“…Cells with reduced AMPK activity increase mitochondrial ROS and experience premature aging [49]. Parkinsonism-causing genes like Parkin, phosphatase and tensin homolog-induced putative kinase (PINK), and DJ-1 impact mitochondrial health via autophagy [50][51][52]. ROS promotes Parkin/PINK-dependent mitophagy [50].…”
Section: Oxidative Stress and Autophagymentioning
confidence: 99%
“…Parkinsonism-causing genes like Parkin, phosphatase and tensin homolog-induced putative kinase (PINK), and DJ-1 impact mitochondrial health via autophagy [50][51][52]. ROS promotes Parkin/PINK-dependent mitophagy [50]. Also, Parkin induces beclin1-mediated autophagic degradation of molecular debris and dysfunctional mitochondria, which prevents oxidative stress [51].…”
Section: Oxidative Stress and Autophagymentioning
confidence: 99%